2003
DOI: 10.1073/pnas.1233721100
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic pressure inhibition of DNA ejection from phage

Abstract: Bacterial viral capsids in aqueous solution can be opened in vitro by addition of their specific receptor proteins, with consequent full ejection of their genomes. We demonstrate that it is possible to control the extent of this ejection by varying the external osmotic pressure. In the particular case of bacteriophage , the ejection is 50% inhibited by osmotic pressures (of polyethylene glycol) comparable to those operative in the cytoplasm of host bacteria; it is completely suppressed by a pressure of 20 atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
381
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(409 citation statements)
references
References 22 publications
(28 reference statements)
24
381
3
Order By: Relevance
“…This force is notably two to three-fold lower than that measured for ϕ29 in a similar ionic condition 6 . However, it is in good agreement with the λ phage DNA ejection force measured by osmotic pressure experiments 35,36 and predicted by theoretical calculations 23,36 . Specifically, an osmotic pressure of ~15 atm was found to be necessary to suppress DNA ejection from a λ mutant having a 41.5 kbp truncated genome 36 , corresponding to an ejection force of ~15 pN 20 .…”
Section: Internal Force Buildup During Packagingsupporting
confidence: 86%
“…This force is notably two to three-fold lower than that measured for ϕ29 in a similar ionic condition 6 . However, it is in good agreement with the λ phage DNA ejection force measured by osmotic pressure experiments 35,36 and predicted by theoretical calculations 23,36 . Specifically, an osmotic pressure of ~15 atm was found to be necessary to suppress DNA ejection from a λ mutant having a 41.5 kbp truncated genome 36 , corresponding to an ejection force of ~15 pN 20 .…”
Section: Internal Force Buildup During Packagingsupporting
confidence: 86%
“…(7) indicates that both osmotic and hydrostatic pressure gradients between the environment and the capsid become zero. These situations correspond to the osmotic suppression experiments [6][7][8][9]12,13]; complete suppression of ejection yields an estimate of the osmotic pressures in a mature phage particle: ∼25 atm for λ, ∼47 atm for SPP1, and ∼16 atm for the deletion mutant T5st(0).…”
Section: Hydrodynamic Model For In Vitro Ejectionmentioning
confidence: 63%
“…Keeping in mind that the model applies only to equilibrium states and not to the dynamics or molecular mechanism of the process, it successfully explains in vitro data for phage λ DNA ejection. Such experiments include the addition of capsid-permeable DNA-condensing agents or capsid-impermeable osmolytes to arrest ejection when the DNA remaining in the capsid reaches equilibrium with the buffer [6][7][8][9] and time-resolved light scattering [10].…”
Section: Introductionmentioning
confidence: 99%
“…The solid material of the virus is described by four parameters, two for the capsid and two for the core. The osmotic pressure inside the capsid, caused by the strong bending of the DNA and the repulsive forces between the neighboring negatively charged chains is of order 2.0 × 10 −3 − 4.0 × 10 −3 GPa, see [12]. The osmotic pressure is added in to the model as an extra pressure at each node in the FE-model, both on the capsid and on the core.…”
Section: Fe-modelmentioning
confidence: 99%
“…In case of phage λ, it has been shown that the capsid strength approximately matches the force exerted by the DNA on the capsid walls [2,12]. This suggests that the capsid strength determines the maximum length of DNA that can be packaged, which in turn is also correlated with the strength of the packaging motor complex [2,13].…”
Section: Introductionmentioning
confidence: 97%